Skip to main content
Solve for x (complex solution)
Tick mark Image
Graph

Similar Problems from Web Search

Share

12\left(3x+10\right)-2\left(\frac{9x-4}{3}-3\left(\frac{x}{2}+\frac{7x-6}{4}\right)\right)\times 12x=6x\left(7x+5\right)
Variable x cannot be equal to 0 since division by zero is not defined. Multiply both sides of the equation by 12x, the least common multiple of x,3,2,4.
36x+120-2\left(\frac{9x-4}{3}-3\left(\frac{x}{2}+\frac{7x-6}{4}\right)\right)\times 12x=6x\left(7x+5\right)
Use the distributive property to multiply 12 by 3x+10.
36x+120-2\left(\frac{9x-4}{3}-3\left(\frac{2x}{4}+\frac{7x-6}{4}\right)\right)\times 12x=6x\left(7x+5\right)
To add or subtract expressions, expand them to make their denominators the same. Least common multiple of 2 and 4 is 4. Multiply \frac{x}{2} times \frac{2}{2}.
36x+120-2\left(\frac{9x-4}{3}-3\times \frac{2x+7x-6}{4}\right)\times 12x=6x\left(7x+5\right)
Since \frac{2x}{4} and \frac{7x-6}{4} have the same denominator, add them by adding their numerators.
36x+120-2\left(\frac{9x-4}{3}-3\times \frac{9x-6}{4}\right)\times 12x=6x\left(7x+5\right)
Combine like terms in 2x+7x-6.
36x+120-2\left(\frac{9x-4}{3}-\frac{3\left(9x-6\right)}{4}\right)\times 12x=6x\left(7x+5\right)
Express 3\times \frac{9x-6}{4} as a single fraction.
36x+120-2\left(\frac{9x-4}{3}-\frac{27x-18}{4}\right)\times 12x=6x\left(7x+5\right)
Use the distributive property to multiply 3 by 9x-6.
36x+120-2\left(\frac{4\left(9x-4\right)}{12}-\frac{3\left(27x-18\right)}{12}\right)\times 12x=6x\left(7x+5\right)
To add or subtract expressions, expand them to make their denominators the same. Least common multiple of 3 and 4 is 12. Multiply \frac{9x-4}{3} times \frac{4}{4}. Multiply \frac{27x-18}{4} times \frac{3}{3}.
36x+120-2\times \frac{4\left(9x-4\right)-3\left(27x-18\right)}{12}\times 12x=6x\left(7x+5\right)
Since \frac{4\left(9x-4\right)}{12} and \frac{3\left(27x-18\right)}{12} have the same denominator, subtract them by subtracting their numerators.
36x+120-2\times \frac{36x-16-81x+54}{12}\times 12x=6x\left(7x+5\right)
Do the multiplications in 4\left(9x-4\right)-3\left(27x-18\right).
36x+120-2\times \frac{-45x+38}{12}\times 12x=6x\left(7x+5\right)
Combine like terms in 36x-16-81x+54.
36x+120-24\times \frac{-45x+38}{12}x=6x\left(7x+5\right)
Multiply 2 and 12 to get 24.
36x+120-2\left(-45x+38\right)x=6x\left(7x+5\right)
Cancel out 12, the greatest common factor in 24 and 12.
36x+120-2\left(-45x+38\right)x=42x^{2}+30x
Use the distributive property to multiply 6x by 7x+5.
36x+120-2\left(-45x+38\right)x-42x^{2}=30x
Subtract 42x^{2} from both sides.
36x+120-2\left(-45x+38\right)x-42x^{2}-30x=0
Subtract 30x from both sides.
36x+120+\left(90x-76\right)x-42x^{2}-30x=0
Use the distributive property to multiply -2 by -45x+38.
36x+120+90x^{2}-76x-42x^{2}-30x=0
Use the distributive property to multiply 90x-76 by x.
-40x+120+90x^{2}-42x^{2}-30x=0
Combine 36x and -76x to get -40x.
-40x+120+48x^{2}-30x=0
Combine 90x^{2} and -42x^{2} to get 48x^{2}.
-70x+120+48x^{2}=0
Combine -40x and -30x to get -70x.
48x^{2}-70x+120=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-70\right)±\sqrt{\left(-70\right)^{2}-4\times 48\times 120}}{2\times 48}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 48 for a, -70 for b, and 120 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-70\right)±\sqrt{4900-4\times 48\times 120}}{2\times 48}
Square -70.
x=\frac{-\left(-70\right)±\sqrt{4900-192\times 120}}{2\times 48}
Multiply -4 times 48.
x=\frac{-\left(-70\right)±\sqrt{4900-23040}}{2\times 48}
Multiply -192 times 120.
x=\frac{-\left(-70\right)±\sqrt{-18140}}{2\times 48}
Add 4900 to -23040.
x=\frac{-\left(-70\right)±2\sqrt{4535}i}{2\times 48}
Take the square root of -18140.
x=\frac{70±2\sqrt{4535}i}{2\times 48}
The opposite of -70 is 70.
x=\frac{70±2\sqrt{4535}i}{96}
Multiply 2 times 48.
x=\frac{70+2\sqrt{4535}i}{96}
Now solve the equation x=\frac{70±2\sqrt{4535}i}{96} when ± is plus. Add 70 to 2i\sqrt{4535}.
x=\frac{35+\sqrt{4535}i}{48}
Divide 70+2i\sqrt{4535} by 96.
x=\frac{-2\sqrt{4535}i+70}{96}
Now solve the equation x=\frac{70±2\sqrt{4535}i}{96} when ± is minus. Subtract 2i\sqrt{4535} from 70.
x=\frac{-\sqrt{4535}i+35}{48}
Divide 70-2i\sqrt{4535} by 96.
x=\frac{35+\sqrt{4535}i}{48} x=\frac{-\sqrt{4535}i+35}{48}
The equation is now solved.
12\left(3x+10\right)-2\left(\frac{9x-4}{3}-3\left(\frac{x}{2}+\frac{7x-6}{4}\right)\right)\times 12x=6x\left(7x+5\right)
Variable x cannot be equal to 0 since division by zero is not defined. Multiply both sides of the equation by 12x, the least common multiple of x,3,2,4.
36x+120-2\left(\frac{9x-4}{3}-3\left(\frac{x}{2}+\frac{7x-6}{4}\right)\right)\times 12x=6x\left(7x+5\right)
Use the distributive property to multiply 12 by 3x+10.
36x+120-2\left(\frac{9x-4}{3}-3\left(\frac{2x}{4}+\frac{7x-6}{4}\right)\right)\times 12x=6x\left(7x+5\right)
To add or subtract expressions, expand them to make their denominators the same. Least common multiple of 2 and 4 is 4. Multiply \frac{x}{2} times \frac{2}{2}.
36x+120-2\left(\frac{9x-4}{3}-3\times \frac{2x+7x-6}{4}\right)\times 12x=6x\left(7x+5\right)
Since \frac{2x}{4} and \frac{7x-6}{4} have the same denominator, add them by adding their numerators.
36x+120-2\left(\frac{9x-4}{3}-3\times \frac{9x-6}{4}\right)\times 12x=6x\left(7x+5\right)
Combine like terms in 2x+7x-6.
36x+120-2\left(\frac{9x-4}{3}-\frac{3\left(9x-6\right)}{4}\right)\times 12x=6x\left(7x+5\right)
Express 3\times \frac{9x-6}{4} as a single fraction.
36x+120-2\left(\frac{9x-4}{3}-\frac{27x-18}{4}\right)\times 12x=6x\left(7x+5\right)
Use the distributive property to multiply 3 by 9x-6.
36x+120-2\left(\frac{4\left(9x-4\right)}{12}-\frac{3\left(27x-18\right)}{12}\right)\times 12x=6x\left(7x+5\right)
To add or subtract expressions, expand them to make their denominators the same. Least common multiple of 3 and 4 is 12. Multiply \frac{9x-4}{3} times \frac{4}{4}. Multiply \frac{27x-18}{4} times \frac{3}{3}.
36x+120-2\times \frac{4\left(9x-4\right)-3\left(27x-18\right)}{12}\times 12x=6x\left(7x+5\right)
Since \frac{4\left(9x-4\right)}{12} and \frac{3\left(27x-18\right)}{12} have the same denominator, subtract them by subtracting their numerators.
36x+120-2\times \frac{36x-16-81x+54}{12}\times 12x=6x\left(7x+5\right)
Do the multiplications in 4\left(9x-4\right)-3\left(27x-18\right).
36x+120-2\times \frac{-45x+38}{12}\times 12x=6x\left(7x+5\right)
Combine like terms in 36x-16-81x+54.
36x+120-24\times \frac{-45x+38}{12}x=6x\left(7x+5\right)
Multiply 2 and 12 to get 24.
36x+120-2\left(-45x+38\right)x=6x\left(7x+5\right)
Cancel out 12, the greatest common factor in 24 and 12.
36x+120-2\left(-45x+38\right)x=42x^{2}+30x
Use the distributive property to multiply 6x by 7x+5.
36x+120-2\left(-45x+38\right)x-42x^{2}=30x
Subtract 42x^{2} from both sides.
36x+120-2\left(-45x+38\right)x-42x^{2}-30x=0
Subtract 30x from both sides.
36x+120+\left(90x-76\right)x-42x^{2}-30x=0
Use the distributive property to multiply -2 by -45x+38.
36x+120+90x^{2}-76x-42x^{2}-30x=0
Use the distributive property to multiply 90x-76 by x.
-40x+120+90x^{2}-42x^{2}-30x=0
Combine 36x and -76x to get -40x.
-40x+120+48x^{2}-30x=0
Combine 90x^{2} and -42x^{2} to get 48x^{2}.
-70x+120+48x^{2}=0
Combine -40x and -30x to get -70x.
-70x+48x^{2}=-120
Subtract 120 from both sides. Anything subtracted from zero gives its negation.
48x^{2}-70x=-120
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{48x^{2}-70x}{48}=-\frac{120}{48}
Divide both sides by 48.
x^{2}+\left(-\frac{70}{48}\right)x=-\frac{120}{48}
Dividing by 48 undoes the multiplication by 48.
x^{2}-\frac{35}{24}x=-\frac{120}{48}
Reduce the fraction \frac{-70}{48} to lowest terms by extracting and canceling out 2.
x^{2}-\frac{35}{24}x=-\frac{5}{2}
Reduce the fraction \frac{-120}{48} to lowest terms by extracting and canceling out 24.
x^{2}-\frac{35}{24}x+\left(-\frac{35}{48}\right)^{2}=-\frac{5}{2}+\left(-\frac{35}{48}\right)^{2}
Divide -\frac{35}{24}, the coefficient of the x term, by 2 to get -\frac{35}{48}. Then add the square of -\frac{35}{48} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-\frac{35}{24}x+\frac{1225}{2304}=-\frac{5}{2}+\frac{1225}{2304}
Square -\frac{35}{48} by squaring both the numerator and the denominator of the fraction.
x^{2}-\frac{35}{24}x+\frac{1225}{2304}=-\frac{4535}{2304}
Add -\frac{5}{2} to \frac{1225}{2304} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x-\frac{35}{48}\right)^{2}=-\frac{4535}{2304}
Factor x^{2}-\frac{35}{24}x+\frac{1225}{2304}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-\frac{35}{48}\right)^{2}}=\sqrt{-\frac{4535}{2304}}
Take the square root of both sides of the equation.
x-\frac{35}{48}=\frac{\sqrt{4535}i}{48} x-\frac{35}{48}=-\frac{\sqrt{4535}i}{48}
Simplify.
x=\frac{35+\sqrt{4535}i}{48} x=\frac{-\sqrt{4535}i+35}{48}
Add \frac{35}{48} to both sides of the equation.